Analysis of the Role of Internal Audit in the Covid-19 Pandemic Study of the Main Inspectorate of the General Election Supervisory Agency - Purba, Vebty Puput (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The Main Inspectorate of the General Election Supervisory Agency, which provided the role of internal oversight services during the COVID-19 Pandemic, stated that they were experiencing obstacles in the implementation of supervision in the form of oversight plans planned in the Annual Supervision Work Program, which were hampered due to the large number of Main Inspectorate auditors who were exposed to COVID-19. This research was conducted to find out the role of internal audit during the COVID-19 pandemic, where obstacles to supervision activities occurred when the auditor was exposed to COVID-19 and the change in traditional supervision methods to remote. This research was carried out based on the realization of the implementation of internal supervision that had been carried out during the pandemic in the public sector, namely non-ministerial government institutions, namely the Main Inspectorate of the General Election Supervisory Agency. The research strategy is a single case study with multiple embedded cases using a descriptive qualitative approach to explore and understand a phenomenon which is then analyzed to conclude. Primary data sources were obtained from the Election Supervisory Body (Bawaslu) Main Inspectorate, including questionnaires, interviews, and internal data, then secondary data in the form of published reports. The research used a combined questionnaire with closed-ended and open-ended questions to determine stakeholders' roles and satisfaction and semi-structured interviews on the effectiveness of monitoring implementation methods. Data analysis used descriptive qualitative from the results of questionnaires and interviews with respondents. This research revealed the role played by the Main Inspectorate during the COVID-19 Pandemic both in policy, planning, and implementation. Assessment of the role of the Internal Auditor then provides recommendations to the Main Inspectorate that can be implemented in the short or long term.